Lanostane-Type Triterpenoids from Scilla scilloides and Structure Revision of Drimiopsin D - Ren, Fu-Cai (Nat Prod Bioprospect, 2015)
ABSTRACT: Two hitherto unknown lanostane-type triterpenoids, namely scillascillol (1) and scillascillone (2), and a hitherto unknown norlanostane-triterpene glycoside, namely scillascilloside B-1 (3), were isolated from the ethanol extract of the whole plants of Scilla scilloides. Their structures were elucidated on the basis of extensive spectroscopic studies. In addition, the structure of drimiopsin D (6a) has been revised as 2,5-dimethoxy-8-methyl-1,3,6-trihydroxyxanthone (6) by reanalysis of the spectroscopic data. GRAPHICAL ABSTRACT: [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13659-015-0076-0) contains supplementary material, which is available to authorized users.